Bringing the water toxicity research into the class to nurture experimental design skills through STEM project-based learning with learning progression - Putri Nurlita Sari; Murni Ramli; Dewi Puspita Sari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Water quality is the part of Sustainable Development Goals (SDGs) 6 and essential for high school biology in Indonesia. Objectives: This study aims to determine the different impact of the STEM project-based learning with the framework of learning progression teaching module on water toxicity research on experimental design skills and examine the impact of STEM project-based learning using the learning progression teaching module on students’ experimental design skills in water toxicity research and to assess students’ responses. Methods: A quantitative quasi-experimental approach with a pretest-posttest control group design was used. The population consisted of 358 class X students at Public Senior High School (PSHS) 2 of Karanganyar in 2024/2025. Cluster random sampling selected class XE 8 as experimental class and XE 7 as control class. Data were collected via tests, questionnaires, observations, and documentation, and analyzed using paired and independent t-tests. Results: The results showed a significant difference between classes (independent t-test significance = 0.000 < 0.05). Student responses were very positive, with average percentages of 85% for research-based practicums, 82% for media, 86% for materials, and 85.5% for project planning and implementation. Conclusion: The study concluded that implementing the STEM PjBL-learning progression module based on water toxicity research improved students’ experimental design skills and was well-received, providing positive learning experiences.